IMPLEMENTATION ANALYSIS GOVERNMENT REGULATION IN LIEU OF LAW NUMBER 2 OF 2020 CONCERNING THE ELECTION OF GOVERNOR, MAYOR AND REGENT IN THE CENTRAL PANDEMI CORONAVIRUS DISEASE 2019 - Indah Satria; Reno Sunarya Pratama (PRANATA HUKUM, 2022)
Regional Autonomy contains an element of supervision (toetzicht), then autonomy is not merely the administration of government to achieve efficiency and effectiveness of government. Autonomy is determined on a territorial basis or on a function basis. The essence of autonomy is independence and freedom to regulate and manage the community itself, which is the function of the government as a household affair in the bonds of a unitary state, autonomy always requires the independence and freedom of an independent government unit. The election of regional heads is carried out in a package together with the deputy regional heads. The regional head and deputy regional head in question include the governor and deputy governor for the province; Regents and deputy regents for districts, mayors and deputy mayors for cities. The reality of Indonesian democracy has undergone many changes and transitions after the reformation. It is not an easy thing for the Indonesian people to go through the democratic transition and then show progress. Major and fundamental steps have been taken to make democracy the direction of the country's goals, namely by making amendments.